Evaluation of Transplanted Aman Rice by Exploiting and Adjusting Existing Technologies - Tahmina Akter Mim; Md. Towkir Ahmed; Uttam Kumer Sarker; Md. Romij Uddin (Archives of Current Research International, 2024)
Varietal differences are a common occurrence in rice cultivation across Bangladesh. Moreover, the application of appropriate management practices (MP) is essential for optimal rice production. Against this backdrop, a study was conducted at the Agronomy Field Laboratory (AFL) of Bangladesh Agricultural University (BAU), Mymensingh, during the aman season from July to December 2023. The aim was to assess the impact of different varieties and MP on the yield and other related attributes of Transplanted Aman (T. aman) rice. The study featured five rice varieties: BR11, BRRI dhan49, BRRI dhan52, BRRI dhan75, and BRRI dhan87 and two MP, namely Farmers’ Practices (FP) and Improved Practices (IP). The experimental design was a split plot, with MP as the main plots and varieties as the subplots, replicated three times. The findings indicated that both the variety of rice and the MP significantly influenced the yield and yield-related traits. Specifically, the variety BRRI dhan87 showed superior performance, yielding the highest plant height (PH) (116.87 cm), panicle length (PL) (25.33 cm), number of effective tillers (NET) hiil-1 (10.33), number of grains panicle-1 (NGP) (129.04), 1000 grain weight (TGW) (26.03 g), Biological yield (BY) (11.88 t ha-1), grain yield (GY) (5.69 t ha-1), Harvest index (HI) (47.81%). Under the MP, the IP recorded the highest NET hiil-1 (10.47), NGP (119.35), and GY (5.48 t ha-1), showing a 13.14% increase in GY over the FP. The combination of BRRI dhan87 and IP achieved the highest GY (6.31 t ha-1). The study concludes that the highest GY of T. aman rice can be achieved by cultivating BRRI dhan87 with IP, although further trials at various locations are recommended before drawing final conclusions.